2019
DOI: 10.3390/min9090534
|View full text |Cite
|
Sign up to set email alerts
|

Re-Os Geochronology and Sulfur Isotopes of the Lyangar W-Mo Deposit: Implications for Permian Tectonic Setting in South Tianshan Orogen, Uzbekistan

Abstract: The Lyangar W-Mo skarn deposit is located in the Nuratau area (western Uzbekistan), South Tianshan Orogen. The skarn system is distributed along the contact zone between the Aktau granitoid and the upper Paleozoic sedimentary rocks. Six molybdenite samples from the Lyangar deposit yielded a Middle Permian Re-Os isochron age of 268.0 ± 12.0 Ma (MSWD = 0.43) and a weighted mean age of 263.8 ± 1.5 Ma (MSWD = 0.22). Molybdenites have low Re contents (12.49 to 16.65 ppm), indicative of a continental crust-dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Bismuth minerals are also widely developed in silverpolymetallic ores and are represented by Ag-bursaite, pilsenite, wittite, galeno-bismuthite, and cannizzarite. Bursaite, platinite, heyrovskite, and weibulite are less common and have been found in the Koytash deposit [17]. Mass spectrometric analysis of monomineralic sulphide fractions in skarn-rare-metal ores has shown that they are elevated in chalcopyrite, but their pyrrhotite content is twice as low.…”
Section: Methodsmentioning
confidence: 99%
“…Bismuth minerals are also widely developed in silverpolymetallic ores and are represented by Ag-bursaite, pilsenite, wittite, galeno-bismuthite, and cannizzarite. Bursaite, platinite, heyrovskite, and weibulite are less common and have been found in the Koytash deposit [17]. Mass spectrometric analysis of monomineralic sulphide fractions in skarn-rare-metal ores has shown that they are elevated in chalcopyrite, but their pyrrhotite content is twice as low.…”
Section: Methodsmentioning
confidence: 99%
“…The Lyangar W-Mo skarn deposit is located in the South Nuratau district at the contact zone between the Middle F I G U R E 1 (a) Schematic tectonic map of Asia, showing the location of the south Tianshan Orogen (modified after Sengör et al, 1993;Zhou et al, 2019). (b) Tectonic map of the south Tianshan Orogen and the location of key mineral deposits (modified after Seltmann et al, 2014;Kempe et al, 2016;Dolgopolova et al, 2017) F I G U R E 2 Schematic geological map of the Lyangar W-Mo deposit (modified from Soloviev & Kryazhev, 2018a) Carboniferous rocks and the Aktau pluton (Figure 2).…”
Section: Deposit Geologymentioning
confidence: 99%
“…(a) Schematic tectonic map of Asia, showing the location of the south Tianshan Orogen (modified after Sengör et al, 1993; Zhou et al, 2019). (b) Tectonic map of the south Tianshan Orogen and the location of key mineral deposits (modified after Seltmann et al, 2014; Kempe et al, 2016; Dolgopolova et al, 2017)…”
Section: Regional Geologymentioning
confidence: 99%
See 2 more Smart Citations